Survival costs of reproduction vary with age in North American red squirrels - Descamps, Sébastien (The Royal Society, 2008)
The costs of reproduction are expected to be higher under unfavourable conditions, so that breeding in years of low food supply should have important costs. In addition, the costs of reproduction may be contingent on the age of individuals, and young growing and old senescent individuals should suffer higher costs than the prime-age ones. We tested these predictions by investigating the costs of reproduction as a function of food availability and age in female North American red squirrels using the long-term data on survival and reproduction. We found that the costs of reproduction were independent of food supply, and we did not detect any trade-off between the current and future reproduction. We also did not detect any survival cost of reproduction for the prime-age females, but found evidence for survival costs in yearlings and old (6 years or above) females with successfully breeding individuals having a lower chance of survival compared with unsuccessful or non-breeding ones. These results supported our prediction that the costs of reproduction depended on the age of female red squirrels and were higher in young growing and old senescent individuals. Our study also indicated that, in contrast to large herbivores, heterogeneity in individual quality and viability selection in red squirrels do not affect the study of trade-offs and of the age variation in life-history traits.